The Influence of Customer Relationship Management, Electronic Word of Mouth, and Price on Purchase Decision - Fauzah Ainun Jazilah; Lia Nirawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the influence of Customer Relationship Management (CRM), Electronic Word of Mouth (eWOM), and Price on consumer purchasing decisions, focusing on Oriflame customers in Probolinggo. The research addresses the competitive dynamics in the beauty and personal care industry, particularly the challenges faced by Oriflame, which maintains a strong market presence despite not utilizing e-commerce platforms. The study applies a quantitative associative method with 100 respondents aged 15–44 using a purposive sampling technique. The independent variables include CRM, eWOM, and Price, while the dependent variable is Purchase Decision. Data were analyzed using multiple linear regression to identify both simultaneous and partial effects of the independent variables. The findings reveal that eWOM and Price have a significant and positive impact on consumer decisions, while CRM shows no significant effect. These results indicate that consumers are heavily influenced by online reviews and price suitability, especially in a competitive and digitally-driven market. The study offers practical recommendations for businesses to enhance eWOM strategies, improve customer interaction, and maintain competitive pricing, which are crucial for sustaining brand loyalty. It also contributes to the academic discourse on digital marketing and consumer behavior in the cosmetic industry, particularly in developing regions where digital literacy and consumer awareness are rapidly increasing.